Polysaccharide of Atractylodes macrocephala Koidz alleviate LPS-induced inflammatory liver injury by reducing pyroptosis of macrophage via regulating LncRNA GAS5/miR-223-3p/NLRP3 axis - Xiaoxiao Chen; Shuzhan Yang; Xin Long; Wanyan Li; Bingxin Li; Cheng Fu; Caoxue Zhen; Danning Xu; Xinliang Fu; Nan Cao (Frontiers in Pharmacology)
IntroductionPyroptosis is a distinctive form of inflammatory cell death, mediated by the activation of the inflammasome, which initiates a potent inflammatory response. Long non-coding RNAs (lncRNAs) modulate pyroptosis by targeting microRNAs and their target genes through a competing endogenous RNA (ceRNA) mechanism. Our previous research has confirmed that Polysaccharide of Atractylodes macrocephala Koidz (PAMK) can alleviate inflammatory liver injury in mice caused by lipopolysaccharide (LPS), but the specific molecular mechanism remains unclear. Additionally, recent studies have identified recruited macrophages in the liver as a key component of both acute and chronic liver inflammation. This study aimed to explore the impact of PAMK on LPS-induced macrophage pyroptosis and its molecular mechanism in mitigating inflammatory liver injury in mice.MethodsC57BL/6 mice were subjected to LPS-induced liver injury with or without PAMK pretreatment. Histopathological analysis, qRT-PCR, Western blot, and ELISA were performed to assess liver damage and pyroptosis markers. In RAW264.7 macrophages, dual-luciferase assays validated ceRNA interactions, while gain/loss-of-function experiments elucidated molecular mechanisms.ResultsIn this study, we found that PAMK alleviated LPS-induced inflammatory liver injury in mice and modulates macrophage pyroptosis through the lncRNA GAS5/miR-223/NLRP3 axis.ConclusionWe conclude that there is a ceRNA relationship between GAS5, miR-223-3p, and NLRP3; PAMK alleviates LPS-induced pyroptosis in macrophages through the lncRNA GAS5/miR-223-3p/NLRP3 axis; and PAMK intervention in the macrophage pyroptosis process subsequently alleviates liver inflammation.